INDUKSI PEMBUNGAAN ANGGREK BULAN (Phalaenopsis amabilis (L.) Blume) DENGAN PEMBERIAN KOMBINASI BENZILADENIN DAN GIBERELIN SECARA IN VITRO - , AGUS SLAMET ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Orchids are ornamental plants that cultivated for the flowers. One of the efforts to improve the orchids breeding is by optimalizing cultivation technique through acceleration of flowering. The objectives of this study are to accelerate the time for flowering of wild Indonesian orchid Phalaenopsis amabilis (L.) Blume by addition of plant growth regulators (PGR) benzyladenin (BA) and Gibberelin (GA3) and to understand about the effect BA and GA3 on flowering of P. amabilis orchid through in vitro culture. The induction of flowering was carried out by addition of PGR: BA (0, 1, 3 and 9) ppm in combination with GA3 (0, 5, 10 and 15) ppm. Seeds were sowed on New Phalaenopsis (NP) medium contained 15% coconut water for 8 weeks, then it was subcultured in NP+(BA-GA3) liquid medium for 9 weeks with shaking 50 rpm. The culture was subsequently transferred onto 2-layer medium (solid: liquid = 5:2), that was maintained at 25 Â°C under short day condition of photoperiodism (8 hours of light-exposured and 16 hours of dark). Observations were made every 2 weeks by measuring the length of leaf and root and counting the number of leaf and roots. The phenotypic data were statistically analyzed using ANOVA, Î± 0.05. Molecular analyses were carried out by Reverse Transcriptase-PCR (RT-PCR) with gene specific primers of Phalaenopsis Orchid Homeobox 1 (POH1) dan Phalaenopsis amabilis Flowering Locus T (PaFT). The accumulation of mRNA of both POH1 and PaFT genes were detected in all of treated plants, although the accumulation of PaFT mRNA was not detected in control/wildtype plant at the same age, inwhich only POH1 mRNA was detected. These data suggest that (BA + GA3) treatment induced activation of PaFT gene in vegetative stage, but interestingly it also extended the activation of the POH1 gene. No flowering can be induced yet, it might be related to the possibility of redundancy and/antagonism occurrence between POH1 and PaFT genes, or due to any post-transcription/translational process has occurred. Some research on protein levels is worth to be explored.